The Role of the Cerebellum in Pain Perception: A Brain SPECT Perfusion Study in Patients with Burn Injuries. Issue 6 (7th July 2020) - Bermo, Mohammed S.; Zacharias, Claudia; Patterson, David; Wilson, Ann; Sharar, Sam; Minoshima, Satoshi; Hoffman, Hunter; Lewis, David H.
ABSTRACT: BACKGROUND AND PURPOSE: Virtual reality (VR) is a promising tool for distraction analgesia. This study aims to compare brain perfusion patterns while patients were undergoing burn wound care in two conditions—VR distraction and control (NoVR). METHODS: With IRB approval, four patients hospitalized for acute burn care (three males and one female) participated in the study. All patients underwent wound care on two consecutive days; 1 day with standard analgesia and adjunctive VR, and the other day with standard analgesia alone, otherwise the wound care was very similar. Tc‐99m ethyl cysteinate dimer was injected during wound care at the time of peak pain. Subjective patient reports on a 0‐10 scale of pain intensity, time spent thinking about pain, and "fun" as well as opioid equivalent usage were analyzed. Voxel by voxel subtraction analysis of brain perfusion Single Photon Emission Computed Tomography (SPECT) images was performed at the group level. Statistical significance threshold was defined as P < .05. RESULTS: Mean group subjective scores (VR, NoVR, statistical significance, and P ‐value) were observed for maximal pain intensity (9.0, 8.8, insignificant, and P = .809), time spent thinking about pain (5.2, 10.0, significant, and P = .015), and fun (6.0, 2.5, significant, and P = .012). Subtraction group analysis demonstrated VR‐induced modulation of brain activity with statistically significant relative suppression of cerebellar activation in the VR compared to intense cerebellar activation in the NoVR environments. CONCLUSION: Relative decrease in cerebellar perfusion based on stringent statistical threshold in the VR environment combined with improved subjective pain experience supports the hypotheses on the role of cerebellum in perception of noxious stimuli.